Digital Dependency or Digital Autonomy? Evaluating the Efficacy of India’s Emerging Policy Framework for Youth Mental Health - Steevan D Souza N; Vandana D Souza N (CV. Doki Course and Training, 2026)
The rapid expansion of digital technology has fundamentally transformed the social, emotional, and academic lives of adolescents. While digital platforms provide opportunities for communication, learning, and creativity, excessive and unregulated use has been associated with rising mental health concerns among young people. In India, increasing smartphone penetration and social media engagement have intensified concerns regarding digital addiction, cyberbullying, sleep disruption, and social comparison anxiety among students (NIMHANS, 2025). These developments have prompted policymakers to explore regulatory frameworks aimed at promoting responsible digital use. The Karnataka Draft Policy 2026 for Responsible Digital Use Among Students represents one of the first structured attempts in India to address the intersection between youth mental health and digital behavior. The policy emphasizes awareness, monitoring, and institutional responsibility. However, the practical implementation of such policies raises critical questions regarding institutional readiness, resource availability, ethical governance, and stakeholder accountability. Without clear operational mechanisms and financial support, policy interventions risk remaining symbolic rather than transformative (OECD, 2021). This paper critically evaluates the effectiveness of emerging digital governance frameworks in protecting youth mental health while preserving digital autonomy. Using the Karnataka Draft Policy as a case study, the paper examines implementation gaps, ethical concerns, and institutional challenges. It further proposes a structured digital guardianship model that emphasizes preventive education, protective systems, and regulatory oversight. The study concludes that sustainable digital governance requires collaboration among schools, parents, technology companies, and government agencies, supported by evidence-based monitoring and continuous policy evaluation.